An evaluation of the effects of nonselective and cardioselective β-blockers on wound healing in Sprague Dawley rats - Raut, Sanket B. (Medknow Publications & Media Pvt Ltd, 2012)
OBJECTIVES: To investigate the effect of a nonselective β-blocker (propranolol) and cardioselective β-blocker (metoprolol) on wound healing in rats using incision and excision wound models and to compare the effect of these drugs on wound healing. MATERIALS AND METHODS: Propranolol and metoprolol were given orally. Sprague Dawley rats of either sex were used. Incision and excision wound models were used to evaluate the wound-healing activity. Effects of metoprolol and propranolol on tensile strength, period of epithelialization, and hydroxyproline content were observed. Histological analysis was done to see collagen deposition and inflammatory infiltrate. STATISTICAL ANALYSIS USED: The data was subjected to analysis of variance (ANOVA) followed by Scheffe's test. P < 0.05 was considered to be statistically significant. Statistical analysis was done using SPSS software version 15.0. RESULTS: Administration of propranolol or metoprolol was shown to decrease tensile strength, delay wound contraction and re-epithelialization, increase inflammatory infiltrate, and reduce collagen density and hydroxyproline levels. CONCLUSIONS: The results suggest that nonselective and cardioselective β-blockers delay wound healing and these effects are mediated by β1-receptors.